2004
DOI: 10.1023/b:jomg.0000048773.95897.5f
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Changes in Mammary Epithelial Cells May Mimic Early Events in Carcinogenesis

Abstract: Studies of human mammary epithelial cells from healthy individuals are providing novel insights into how early epigenetic and genetic events affect genomic integrity and fuel carcinogenesis. Key epigenetic changes, such as the hypermethylation of the p16 (INK4a) promoter sequences, create a previously unappreciated preclonal phase of tumorigenesis in which a subpopulation of mammary epithelial cells are positioned for progression to malignancy (Romanov et al. , 2001, Nature , 409:633-637; Tlsty et al. , 2001, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 44 publications
4
57
0
3
Order By: Relevance
“…In a majority of ducts and lobules including TDLU in normal mammary tissues, cytokeratins 5/6 and 17 were expressed in both basal and luminal cells, confi rming the previously described variability of expression of these basal cytokeratins and their relationship to cellular origin 30 . Cytokeratin 5 and 17 have also been found in a subset of breast cancer patients with a poor clinical outcome 32 .…”
Section: Discussionsupporting
confidence: 83%
“…In a majority of ducts and lobules including TDLU in normal mammary tissues, cytokeratins 5/6 and 17 were expressed in both basal and luminal cells, confi rming the previously described variability of expression of these basal cytokeratins and their relationship to cellular origin 30 . Cytokeratin 5 and 17 have also been found in a subset of breast cancer patients with a poor clinical outcome 32 .…”
Section: Discussionsupporting
confidence: 83%
“…These advances in the knowledge of the breast methylome strongly indicate that DNA hypermethylation plays a crucial role in initiation, promotion and maintenance of breast carcinogenesis, which cooperatively and synergistically interact with other genetic alterations to promote the development of breast cancer. For example, human mammary epithelial cells (HMECs) that gained the ability to emerge from the first transient growth plateau lost p16INK4A expression concurrently with hypermethylation of p16INK4A promoter, indicating that loss of tumor-suppressor function of p16INK4A is required for HMECs to gain growth competency by successfully bypassing the stage of cell senescence Tlsty et al, 2004). This finding is consistent with other studies where the life span of stem cells could be extended by germline loss of this gene (Janzen et al, 2006).…”
Section: Epigenetic Modifications and Breast Cancersupporting
confidence: 86%
“…We and others have previously shown that the silencing and DNA methylation of the p16 INK4A locus occurs during selection (9,10,(12)(13)(14)(15), and it has been suggested that epigenetic deregulation of p16 INK4A occurs commonly in premalignant breast lesions. Indeed, rare foci of morphologically normal epithelial cells with hypermethylation of the tumor suppressor gene p16 INK4A have been identified in vivo in disease-free breast tissue (12) and these foci have been hypothesized to be precursors to cancer (16).…”
Section: Introductionmentioning
confidence: 99%